Pemanfaatan Limbah Cangkang Kijing untuk Diversifikasi Produk Sarapan Siap Saji Diperkaya Kalsium di Kota dan Kabupaten Bogor - Erni Rustiani; Sata Yoshida Srie Rahayu; Mira Miranti (Institut Pertanian Bogor, 2015)
Waste processing of mussel’s shell into flour and extract the calcium content has been done as community service activities. Mussel’s shell flour that added into breakfast product was enrichment by calcium. The products are flakes and cereal drinks. Skill of making cereal flakes and beverages was expected can empower the majority of women who have limited time in the development of healthy families so that they can provide food that is practically nutrients and mineral content enough. It is an opportunity to improve the economic welfare of society, especially poor families to get family extra income. Target of community service were women who are members of the Integrated Improvement Program Role of Women Towards Healthy and Prosperous Families (P2WKSS) in Tegalega, Bogor City and women of PKK Kemang’s Village, Bogor District. The activity were implemented in three stages, the first is the socialization of understanding of the fulfilment source of calcium and utilization of waste mussel’s shell. The second is the manufacturing skills training cereal flakes and drinks made from mussel’s flour as well as a way of packaging and labelling flakes. The third is evaluation through competition of participants to make some variants cereal flakes and beverage packaging. The results of activities demonstrated an understanding the use of flour calcium enrichment by shells in breakfast and drink products of flakes cereal. The results of training activities were evaluated through competitions showed the PKK member was able to either create a flakes product and cereal drink with different variations. The package was quite good so that flakes of such products worthy for sale.